An Alternative Anionic Polyelectrolyte for Aqueous PEDOT Dispersions: Toward Printable Transparent Electrodes1. Issue 29 (1st June 2015) - Hofmann, Anna I.; Smaal, Wiljan T. T.; Mumtaz, Muhammad; Katsigiannopoulos, Dimitrios; Brochon, Cyril; Schütze, Falk; Hild, Olaf R.; Cloutet, Eric; Hadziioannou, Georges
Abstract Organic conducting polymers are promising electrode materials for printable organic electronics. One of the most studied conducting polymers is PEDOT:PSS, which is sufficiently conductive and transparent, but which shows some drawbacks, such as hygroscopicity and acidity. A new approach to stabilize PEDOT in aqueous dispersions involves the replacement of PSS with a basic polyanion based on a polystyrene backbone with (trifluoromethylsulfonyl)imide (TSFI) side groups. The PEDOT:PSTFSIK dispersions were obtained by oxidative polymerization of EDOT in an aqueous PSTFSIK solution and were characterized with regard to their composition, morphology, doping, rheological behavior, and optoelectronic performance. The PEDOT:PSTFSIK dispersions showed excellent printability and good optoelectronic performance (238 Ohm sq−1 at 91 % transmittance, σ>260 S cm−1) and were successfully integrated as flexible electrodes in OLED and OPV devices.